PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V - Yuni Eka Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of visual, auditory, and kinesthetic learning styles on the Indonesian language learning outcomes of fifth-grade students at SD Negeri 01 Wonogiri. The background of this research is based on the low literacy achievement of students, as reflected in the National Education Report. One of the contributing factors to this condition is the lack of attention to the diversity of students’ learning styles. This research employs a quantitative approach with a survey method and applies regression analysis techniques to examine the relationships among variables. The subjects of the study were fifth-grade students at SD Negeri 01 Wonogiri. The findings reveal that visual, auditory, and kinesthetic learning styles have a significant influence on students’ Indonesian language learning outcomes, both partially and simultaneously. The implications of this study highlight the urgency of implementing varied and adaptive teaching strategies to accommodate differences in students’ learning styles and to promote more optimal learning outcomes.